Physiotherapy Management To Prevention Of Covid-19 By Improved Physical Activity In Elderly - Andung Maheswara Rakasiwi; Ade Irma Nahdliyyah (Procedia of Social Sciences and Humanities, 2021)
Coronavirus 2019 (COVID-19), is an acute respiratory syndrome caused by the corona-2 virus (SARS-CoV-2). Elderly is a condition where the tissue's ability to repair itself or replace itself slowly disappears and maintains its normal structure and function so that it cannot survive. Problems that may arise, it is necessary to improve or improve the physical condition of the elderly, which can help them to maintain their health in their retirement. This study aims to reduce the impact of the Covid 19 pandemic on the elderly, provide an overview of the physical problems of Covid 19 in the elderly and prevention of Covid 19 in the elderly. This type of research is a type of experimental research that uses a pre- experimental research design in the form of a one-group pretest-posttest design. showed a probability value with a value of p <0.05. These results indicate that physiotherapy management in the elderly during Covid 19 provided support for increased physical activity, so that the risk of being exposed to Covid 19 can be eliminated. management physiotherapy for covid 19 the p value is 0.000, p value <0.05, this shows that there are significant results between the pre test and post test on the physiotherapy management of the elderly during the Covid 19 pandemic. For the physical activity for elderly the p value is 0,015 this shows that the physical activities carried out by the elderly during a pandemic have not changed but can be given motivation to do physical activity. For the information fear of ctracting corona virus p value 0,007 this shows that the information on physical activity provided by physiotherapy does not change the fear of the elderly still being exposed to Covid